Comparative genomics of multi-drug resistant Pseudomonas aeruginosa / Muhammad Adib Abd Wahab - Muhammad Adib , Abd Wahab (2019)
Pseudomonas aeruginosa is an opportunistic Gram-negative bacterium that inhabits diverse environments and is also one of the leading pathogens causing nosocomial infections in humans. Multidrug resistant (MDR) P. aeruginosa is of worldwide concern because of high rates of antibiotic resistance. The objectives of the study were to compare the genetic content, antimicrobial resistance genes and virulence genes of two clinical P. aeruginosa strains, PAC08 and PAC17, from a tertiary hospital in Kuala Lumpur. In addition, the intraspecies phylogenetic relationship between Malaysian P. aeruginosa and other geographically located strains was determined. The whole genome sequences of PAC08 and PAC17 were assembled using bioinformatics tools to determine the genomic content, antibiotic resistance and virulence-associated genes and phylogeny. Phylogenetic analysis amongst Malaysian and global strains were determined based on 16S rRNA gene, 23S rRNA gene, multilocus sequence typing (MLST) and whole-genome single nucleotide polymorphism (SNP). Genome assembly of PAC08 and PAC17 showed that both strains have similar genome size, 6.89 Mbp and 6.84 Mbp, respectively. MLST analysis showed that sequence type (ST) of PAC08 was ST1076 which is rarely found while the ST of PAC17 is ST235, a more common ST circulating in Europe, China, Japan and Brazil. PAC08, an urine strain has more bacteriophages while the blood strain PAC17 has more insertion sequence (IS). PAC17 which is a multidrug resistant strain, has high number of genes associated with drug resistance involving efflux pumps and antibiotic inactivation enzymes. A similar number of virulence genes were detected in PAC08 and PAC17. Clustered regularly interspaced short palindromic repeat (CRISPR) analysis revealed that PAC08 has three CRISPR loci and five questionable CRISPR loci while PAC17 only has two questionable CRISPR loci. Pan genome analysis defined PAC08 and PAC17 as open-pangenome, which have large genomes and high horizontal rate of gene transfer. Through phylogenetic analysis based on 16S and 23S rRNA genes, MLST, and SNP, PAC17 was grouped together with a few MDR P. aeruginosa strains from Japan and United Kingdom while PAC08 was closely related with another MDR P. aeruginosa strain isolated from Malaysia. As a conclusion, even though PAC08 and PAC17 were isolated from different source, there was not much difference in term of genomic structures. Genomic contents of PAC08 and PAC17 are diverse with the presence of a variety mobile genetic elements such as insertion sequence, bacteriophages, and integrons. The major element contributing to the multidrug resistance in P. aeruginosa is multidrug efflux pumps which efficiently efflux out antibiotics. Moreover, the presence of resistance gene elements in PAC08 and PAC17 had increased resistance towards aminoglycoside, β-lactamase, Fosfomycin, Macrolide, Phenicol and sulphonamide. Various virulence factors were found in PAC08 and PAC17 which probably play roles in pathogenesis. This analysis had provided an insight into virulence and pathogenesis of MDR P. aeruginosa of Malaysia strains which will assist in preventing and controlling transmission of MDR P. aeruginosa.